(untitled) (Research, Society and Development, 2022)
Suicide is a worldwide phenomenon, in 2015 about 800,000 suicides were documented worldwide, responsible for 1.4% of premature deaths. Most, worldwide, are related to psychiatric illnesses with numbers at least 10 times higher than in the general population. Suicidal behavior is influenced by several precipitating factors and understanding them is essential for the improvement of preventive measures aimed at reducing the burden and mortality of the disease. In Brazil, suicide rates can reach 6.5 deaths per 100,000 inhabitants. It is estimated that each suicide affects a wide range of people involved and who may need medical services or support after exposure. The present study addresses the prevalence of suicide attempts at the Emergency Care Unit - UPA Veneza, an urgency/emergency service in the municipality of Cascavel - Paraná, from June 2019 to June 2020. In order to analyze the occurrence of cases of attempted suicide from the Venice UPA, comparing them with the rates described in the current national scenario, a total of 130 medical records of patients who had their diagnosis as a suicide attempt were investigated.